Reaction mechanisms and products of lead with C6H6 and C6H5OH in incineration of sludge: A theoretical exploration. (17th November 2020) - Lu, Chenggang; Tang, Yizhen; Tong, Yi; Zhao, Hui; Cheng, Zhuang; Sun, Jingyu
Abstract: In this work, the reactions of Pb and PbO with benzene (C6 H6 ) and phenol (C6 H5 OH) during sludge incineration were investigated using quantum chemistry methods. Result indicates that Pb reacts with two organics via insertion mechanism to form C6 H5 PbH, C6 H5 OPbH, C6 H5 PbOH, and m‐, o‐, p‐ HPbC6 H4 OH. The energy barriers are modest to overcome, and all products are rather stable with their relative energy from around −130 to −250 kJ/mol; therefore, Pb could be formed as Pb‐organic compounds deposited in bottom ash or fly ash. Moreover, C6 H5 OPbH is the most feasible products thermodynamically and kinetically. In presence of oxygen, Pb might be oxidized to be PbO firstly, and C6 H5 PbOH and o‐ HOPbC6 H4 OH were formed when PbO as reactant; the corresponding barriers are high to be 114 and 53 kJ/mol, respectively, indicating these organic‐metal compounds are difficult to generate during incineration of sludge. It implies that O2 free condition is more feasible for Pb to be deposited as compounds in bottom slag or fly ash. Thus, the secondary treatment of bottom slag or fly ash is necessary to reduce the harm of Pb‐contained compounds after sludge incineration. Abstract : The reactions of Pb and PbO with benzene (C6 H6 ) and phenol (C6 H5 OH) during sludge incineration were investigated using quantum chemistry methods. C6 H5 OPbH is the most feasible products theromdynamically and kinetically without extra oxygen. C6 H5 PbOH and o ‐HOPbC6 H4 OH were formed when PbO as reactants with extra oxygen supplied. O2 free condition is more feasible for Pb to be deposited as compounds in bottom slag or fly ash.